1983
DOI: 10.1152/ajpregu.1983.245.5.r684
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate feeding speeds reversal of enhanced glucose uptake in muscle after exercise

Abstract: Muscle contractile activity results in an increase in glucose uptake rate that can persist for hours. This study was undertaken to determine the effect of carbohydrate repletion on reversal of an exercise-induced increase in glucose uptake. Rats were exercised by swimming. In rats studied 60 min after exercise, muscle glycogen content was 75% depleted and glucose uptake rate was increased. The effect of exercise on glucose uptake was reversed, and glycogen concentration had increased 44 mumol/g muscle, within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 0 publications
4
33
0
Order By: Relevance
“…Studies in perfused rat hindlimbs (Young et al 1983) and in incubated epitrochlearis muscles (Cartee et al 1989) have demonstrated that the rate at which this increase is reversed in vivo is to a large extent determined by the diet ingested during the post-exercise period. Thus, carbohydrate deprivation slows, whereas carbohydrate feeding speeds reversal of the increase.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in perfused rat hindlimbs (Young et al 1983) and in incubated epitrochlearis muscles (Cartee et al 1989) have demonstrated that the rate at which this increase is reversed in vivo is to a large extent determined by the diet ingested during the post-exercise period. Thus, carbohydrate deprivation slows, whereas carbohydrate feeding speeds reversal of the increase.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose uptake was markedly increased 60 min after exercise. Eighteen hours later, only ϳ50% of the increase in glucose uptake had worn off in rats fed a carbohydrate-free diet, whereas the increase in uptake had completely reversed in rats fed carbohydrate to raise muscle glycogen (68). Because there was no insulin in the perfusion medium, we erroneously attributed the persistent increase in glucose uptake 18 h after exercise to a slowing of reversal of the exercise-induced, insulin-independent increase in glucose uptake as a result of prevention of glycogen repletion.…”
Section: Persistent Effect Of Exercise On Muscle Glucose Transportmentioning
confidence: 99%
“…It was not clear whether this persistent effect of exercise was due to a persistent increase in insulin action or to a persistence of the exercise-induced, insulin independent increase in glucose transport that was additive to the effect of insulin. A follow-up experiment was, therefore, performed (68). Rats were exercised to deplete glycogen, and glucose uptake by perfused muscles was measured 60 min and 18 h after exercise in the absence of insulin.…”
Section: Persistent Effect Of Exercise On Muscle Glucose Transportmentioning
confidence: 99%
“…To try to distinguish between these possibilities, Jack Young and others in my lab exercised rats to deplete muscle glycogen and measured glucose uptake and 3-MG accumulation by their perfused muscles 1 h or 18 h later (133). Both glucose uptake and 3-MG accumulation were markedly increased 60 min after exercise.…”
Section: Reversal Of Enhanced Glucose Uptake After Exercisementioning
confidence: 99%